BALANCED SCORECARD UNTUK MENILAI KINERJA PERUSAHAAN (BARAYA TRAVEL BANDUNG) - Delly Sukmanawan; Azhar Affandi (Faculty of Economic and Business, University of Pasundan, 2019)
Uncertainty in an increasingly competitive business environment, especially in the raising and emergence of several new companies in travel transportation services, should encourage a company to be able to have better performance to compete. Companies are faced with various threats and opportunities that emerge in the business environment, thus exposed to the uniformity of the company’s performance measurement tools as an instrument of the company’s performance evaluation. Measurement of company performance applied by Baraya Travel Bandung still use traditional performance measurement, incomprehensive and not optimal yet. Baraya Travel Bandung needs a performance measurement tool that can provide an overview of the overall achievement of the company’s business. The design of performance measurement tool that became the purpose of this research is Balanced Scorecard. The design of performance measuring tools using the Balanced Scorecard begins with translating the company’s vision, mission and strategic objectives that are linked into four perspectives in the Balanced Scorecard.